Optical design and performance of the biological small‐angle X‐ray scattering beamline at the Taiwan Photon Source. (18th October 2021) - Liu, D.-G.; Chang, C.-H.; Chiang, L.-C.; Lee, M.-H.; Chang, C.-F.; Lin, C.-Y.; Liang, C.-C.; Lee, T.-H.; Lin, S.-W.; Liu, C.-Y.; Hwang, C.-S.; Huang, J.-C.; et al.
Abstract : The optical design and performance of the BioSAXS beamline at the Taiwan Photon Source are reported Abstract : The optical design and performance of the recently opened 13A biological small‐angle X‐ray scattering (SAXS) beamline at the 3.0 GeV Taiwan Photon Source of the National Synchrotron Radiation Research Center are reported. The beamline is designed for studies of biological structures and kinetics in a wide range of length and time scales, from angstrom to micrometre and from microsecond to minutes. A 4 m IU24 undulator of the beamline provides high‐flux X‐rays in the energy range 4.0–23.0 keV. MoB4 C double‐multilayer and Si(111) double‐crystal monochromators (DMM/DCM) are combined on the same rotating platform for a smooth rotation transition from a high‐flux beam of ∼4 × 10 14  photons s −1 to a high‐energy‐resolution beam of Δ E / E ≃ 1.5 × 10 −4 ; both modes share a constant beam exit. With a set of Kirkpatrick–Baez (KB) mirrors, the X‐ray beam is focused to the farthest SAXS detector position, 52 m from the source. A downstream four‐bounce crystal collimator, comprising two sets of Si(311) double crystals arranged in a dispersive configuration, optionally collimate the DCM (vertically diffracted) beam in the horizontal direction for ultra‐SAXS with a minimum scattering vector q down to 0.0004 Å −1, which allows resolving ordered d ‐spacing up to 1 µm. A microbeam, of 10–50 µm beam size, is tailored by a combined set of high‐heat‐load slits followed by micrometre‐precision slits situated at the front‐end 15.5 m position. The second set of KB mirrors then focus the beam to the 40 m sample position, with a demagnification ratio of ∼1.5. A detecting system comprising two in‐vacuum X‐ray pixel detectors is installed to perform synchronized small‐ and wide‐angle X‐ray scattering data collections. The observed beamline performance proves the feasibility of having compound features of high flux, microbeam and ultra‐SAXS in one beamline.